De Novo bone metastasis in breast cancer: tumor biology and survival outcomes in a retrospective study from Pakistan - Eman Anwar; Aqsa Amjad; Akbar Jaleel Zubairi; Muhammad Maisam Ali; Sana Zeeshan (BMC Cancer)
Abstract Purpose Breast cancer is the leading cause of cancer-related deaths among women, with 20–30% of early-stage patients eventually developing metastases, often in bones. Despite the high incidence, risk factors for de novo bone metastasis are understudied in local populations. Methods This single-center, retrospective study was conducted at Aga Khan University Hospital, Karachi. Patient demographics, tumor characteristics, and risk factors were assessed. Patients with de novo bone metastasis were compared to non-stage IV cases using binary univariate and multivariate logistic regression, with significance set at p < 0.05. Results Among 2565 patients, 93 (3.6%) presented with bone only metastasis (BOM) and 135 (5.3%) presented with bone and visceral metastasis together. The median age was 51 years, with females predominating. Multivariate analysis revealed that triple-negative breast carcinoma had lower odds (OR 0.36, 95% CI (0.16–0.79) p < 0.001). Advanced T and N stages and tumor grade II were linked to higher odds of bone-only metastasis. The 2-year overall survival of participants with BOM was 93% (CI: 83.7–97%). Conclusion This study identifies key risk factors that provide the basis for early detection and intervention strategies. While it has a few limitations, these findings can guide future research and inform risk assessment models for more diverse populations.